E-241 A prospective, multicenter study assessing the embolization of intracranial aneurysms using wave™ extra soft coils, a part of the penumbra smart coil® system: study protocol for SURF. (4th August 2020) - Schirmer, C; Kaminsky, I; Chaudry, M; Zaidat, O; Alshekhlee, A; Ramakrishnan, P; Taqi, M
Abstract : Introduction/Purpose: Initial clinical evidence has shown that coiling with the SMART COIL® System (Penumbra, Inc.) is a safe and durable treatment option for intracranial aneurysms. 1–5 The WAVE™ Extra Soft Coil (WAVE) is part of the SMART Coil System and is specifically designed as a fill and finish coil. The primary objective of the SURF study, a post-market registry, is to assess the utility of WAVE as a fill and finish coil to support adequate occlusion at one year follow-up. A secondary objective is to compare the ability of digital subtraction angiography (DSA) and magnetic resonance angiography (MRA) to detect incomplete occlusion in the coiled aneurysms. Materials and Methods: SURF is a post-market, prospective, multicenter, single-arm, observational study that will enroll approximately 800 consecutive patients at up to 50 centers in North America. Patients age ≥ 18 years, having embolization of intracranial aneurysms, with WAVE as the final finishing coil and Penumbra SMART COIL System accounting for at least 75% of total number of coils implanted, will be included. All subjects will be followed for approximately 1 year. The primary efficacy endpoint is adequate occlusion defined as Raymond-Roy Occlusion Class I and II at final follow-up. The primary safety endpoints are serious adverse events (SAE) within 24 hours post-procedure and device-related SAE up to 7 days or discharge. Imaging will be analyzed by an independent core lab to assess aneurysm occlusion rates at follow-up. Imaging modalities include DSA, computed tomography angiography (CTA), and/or MRA. A comparative analysis between imaging modalities will be performed for patients with DSA and MRA. Results: The trial is currently recruiting. Enrollment began November 2019 and the estimated date for study completion is June 2023. Imaging and clinical data collection and core laboratory review are ongoing. Conclusion: We report the design of the SURF study, a post-market registry that evaluates the safety and performance of the Penumbra SMART COIL System, including WAVE as a fill and finish coil, in the treatment of intracranial aneurysms. References: Daniel B, Henrik S, Ioannis T, Veit R, Marios-Nikos P. SMART coils for intracranial aneurysm repair - a single center experience. BMC Neurol . 2020 Jan 29;20(1):38. Sokolowski JD, Ilyas A, Buell TJ, Taylor DG, Chen CJ, Ding D, Raper DMS, Liu KC. SMART coils for intracranial aneurysm embolization: Follow-up outcomes. J Clin Neurosci 2019 Jan;59:93–97. Ilyas A, Buell TJ, Chen CJ, Ding D, Raper DMS, Taylor DG, Sokolowski JD, Liu KC. SMART coils for intracranial aneurysm embolization: Initial outcomes. Clin Neurol Neurosurg 2018 Jan;164:87–91. Spiotta AM, Fargen KM, Lena J, Chaudry I, Turner RD, Turk AS, Huddle D, Loy D, Bellon R, Frei D. Initial Technical Experience with the SMART Coil for the Embolization of Intracranial Aneurysms. World Neurosurg 2017 Jan;97:80–85. Stapleton CJ, Torok CM, Patel AB. Early experience with the Penumbra SMART coil in the endovascular treatment of intracranial aneurysms: Safety and efficacy. Interv Neuroradiol 2016 Dec;22(6):654–658. Disclosures: C. Schirmer: None. I. Kaminsky: None. M. Chaudry: None. O. Zaidat: None. A. Alshekhlee: None. P. Ramakrishnan: None. M. Taqi: None.